PANDANGAN ULAMA DAN INTELEKTUAL MUSLIM TERHADAP KONSEP ISLAM KULTURAL DAN ISLAM FUNDAMENTAL DALAM PEMBANGUNAN KEISLAMAN DI PADANGSIDIMPUAN - Lubis, Agus Salim (Institut Agama Islam Negeri Padangsidimpuan, 2014)
AbstractIn Padangsidimpuan has evolved Cultural Islamic religious thought. Therefore the majority of scholars and muslim communities in Padangsidimpuan more likely to Cultural Islamic religious thought, namely that bring the Islam with culture, and perform religious traditions that do not exist at the time of the Holy Apostles; such as the Great Feast Days of Islam, Dhikr Akbar, Perwiridan, and others. Then in the last few years has grown to a group of scholars and muslim religious community sensible of Islam Fundamental, which preach a return to the Qur'an and Hadith are pure and intact, and leave the religious traditions that do not exist at the time of the Holy Apostles, as it is a heresy is heresy. This has led to mutual blame and confuse some people lay. For that, need to be investigated responses scholars and muslim intellectuals on the issue.Key Word: Islamic, Cultural, Fundamental, scholars, intellectuals.